ISOLATION AND IDENTIFICATION FLAVONOID COMPOUND FROM THE STEM BARK OF Saccopetalum horsfieldii BENN - Mahmiah Mahmiah (Indonesian Journal of Chemistry, 2006)
Isolation and identification flavonoid compound from the stem bark of Indonesian plant Saccopetalum horsfieldii Benn. Annonaceae family have been done. Extraction was carried out by maseration method using methanol at room temperature, the product was then extracted by n-hexane and etil acetate. Etil acetate extract separation carried out by liquid vacuum column chromatography and flash column chromatography. The product purificated by recristalization using acetone p.a. into yellow solid that having melting point of 224-226 °C. The structure of flavonoid compound was determinated by spectroscopy method : UV-vis, IR, 1H-NMR and 12C-NMR. The flavonoid compound known as quercetin-3,7-dimetil eter or 3,7-dimetoksi quercetin.